A Qualitative Study on Midwives' Perceptions of Physiologic Birth in Singapore. Issue 4 (October 2018) - Wong, Cassandra Yuit Wah; Shorey, Shefaly; Liew, Kelly; He, Hong-Gu; Koh, Serena S. L.
Abstract : Midwives are advocates for parturients, and their actions and attitudes can influence a woman's experience during childbirth. Hence, it is valuable to examine midwives' perceptions of physiologic birth in an obstetric-led environment. A descriptive, qualitative study design was utilized. Semistructured face-to-face interviews were conducted with 10 registered midwives from the birthing suite of a public hospital in Singapore. Data were analyzed using thematic analysis. Three major themes were (1) perceptions of physiologic birth, (2) perceived facilitators of physiologic birth, and (3) perceived barriers to physiologic birth. Interestingly, senior midwives in this study experienced more negative outcomes with physiologic birth, resulting in apprehension and reduced confidence levels. This study contributed to the understanding of midwives' perceptions regarding facilitators and barriers to physiologic birth. Factors such as supporting birthing team and antepartum education could be useful in supporting physiologic birth. However, advanced age of some of the midwives was found in this study to be a barrier to physiologic birth.